Rapid, simple and stability-indicating determination of polyhexamethylene biguanide in liquid and gel-like dosage forms by liquid chromatography with diode-array detection - Markus Küsters; Sören Beyer; Stephan Kutscher; Harald Schlesinger; Michael Gerhartz (Elsevier, 2013)
A rapid and simple method for the determination of polyhexamethylene biguanide (polyhexanide, PHMB) in liquid and gel-like pharmaceutical formulations by means of high performance liquid chromatography coupled to diode-array detection (HPLCâDAD) was developed. Best separation was achieved using a cyanopropyl bonded phase (Agilent Zorbax Eclipse XDB-CN column 4.6mmÃ75mm with particle size of 3.5Î¼m) as well as gradient elution consisting of acetonitrile/deionized water at a flow rate of 1.0mL/min. The optimized and applied chromatographic conditions permitted separation of polyhexanide from interacting matrix with subsequent detection at a wavelength of 235nm with good sensitivity. The method validation was carried out with regard to the guidelines for analytical procedures demanded by the International Conference on Harmonisation (ICH). Mean recoveries of 102% and 101% for gel-like as well as liquid preparations were obtained. Suitable repeatability as well as intermediate precision could be achieved with limits of detection â¤0.004mg/mL for both formulations, equivalent to â¤0.004% PHMB concerning sample preparation. Determination of PHMB was accomplished without tedious sample preparation. Interacting matrix could be eliminated by the chromatographic procedure with excellent performance of system suitability. All analytical requirements were fulfilled permitting a reliable and precise determination of PHMB in pharmaceuticals. Furthermore, the developed method was applied to stability testing of pharmaceutical preparations containing PHMB. Keywords: Polyhexamethylene biguanide, Polyhexanide, Pharmaceuticals, High performance liquid chromatography